2018
DOI: 10.1016/j.jcpa.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Basaloid Squamous Cell Carcinoma in a Dog

Abstract: A 9-year-old neutered male crossbred dog with a 4-week history of progressive vestibulocerebellar signs was presented for necropsy examination. Gross examination revealed neoplastic growth in the lungs, thoracic lymph nodes, left kidney and cerebellum. Microscopically, the tumour consisted of an infiltrative, densely cellular, basaloid epithelial neoplastic growth with extensive areas of abrupt keratinization. Immunohistochemically, neoplastic cells expressed p63 and partially expressed cytokeratins 5/6. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the human World Health Organization (WHO) classification, basaloid carcinoma has been classified under tumors of the thymus [ 12 ]. There is no definitive tumor classification for basaloid carcinoma in animals, and there has only been one case report about basaloid squamous cell carcinoma (BSCC) occurring in dogs [ 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the human World Health Organization (WHO) classification, basaloid carcinoma has been classified under tumors of the thymus [ 12 ]. There is no definitive tumor classification for basaloid carcinoma in animals, and there has only been one case report about basaloid squamous cell carcinoma (BSCC) occurring in dogs [ 10 ].…”
mentioning
confidence: 99%
“…In animals, there have only been two reports about basaloid carcinoma. One report was about BSCC occurring in the canine lung [ 10 ], and the other report was about a pulmonary tumor in a dolphin, which was diagnosed as a poorly differentiated squamous cell carcinoma, but its histological features suggested that it might have been a BSCC [ 4 ]. The occurrence of basaloid carcinoma in animals is rare, and to the best of our knowledge, this is the first report about basaloid carcinoma in the mediastinal cavity in animals (two dogs).…”
mentioning
confidence: 99%